Progressive fibrosing interstitial lung disease in rheumatoid arthritis: A retrospective study - Denis, Anna; Henket, Monique; Ernst, Marie; Maes, Nathalie; Thys, Marie; Regnier, Céline; Malaise, Olivier; Frix, Anne-Noëlle; Gester, Fanny; Desir, Colin; Meunier, Paul; Louis, Renaud; et al. (Frontiers in Medicine, 2022)
Background and objective: Rheumatoid arthritis associated-interstitial lung disease (RA-ILD) is the most common pulmonary manifestation of rheumatoid arthritis (RA) and an important cause of mortality. In patients suffering from interstitial lung diseases from different etiologies (including RA-ILD), a significant proportion is exhibiting a fibrotic progression despite immunosuppressive therapies, defined as progressive fibrosing interstitial lung disease (PF-ILD). Here, we report the frequency of RA-ILD and PF-ILD in all RA patients’ cohort at University Hospital of Liège and compare their characteristics and outcomes. Methods: Patients were retrospectively recruited from 2010 to 2020. PF-ILD was defined based on functional, clinical and/or iconographic progression criteria within 24 months despite specific anti-RA treatment. Results: Out of 1500 RA patients, about one third had high-resolution computed tomography (HRCT) performed, 89 showed RA-ILD and 48 PF-ILD. RA-ILD patients were significantly older than other RA patients (71 old of median age versus 65, p<0.0001), with a greater proportion of men (46.1% versus 27.7%, p<0.0001) and of smoking history. Nonspecific interstitial pneumonia pattern was more frequent than usual interstitial pneumonia among RA-ILD (60.7% versus 27.0%) and PF-ILD groups (60.4% versus 31.2%). The risk of death was 2 times higher in RA-ILD patients (hazard ratio 2.03 [95% confidence interval 1.15-3.57], p<0.01) compared to RA. Conclusion: We identified a prevalence of PF-ILD of 3% in a general RA population. The PF-ILD cohort did not seem to be different in terms of demographic characteristics and mortality compared to RA-ILD patients who did not exhibit the progressive phenotype yet.